TEACHING STUDENTS’ ARGUMENTATIVE STRATEGIES BASED ON SHORT FILMS (BASIC SECONDARY SCHOOL, ENGLISH) (Intent Research Scientific Journal, 2023)
In this article, the teaching of communicative strategies of students of the basic secondary school for the formation of foreign language communicative competence, in particular successful competently structured communication is considered. This study is largely an experiment involving students. The role of the teacher is reduced to the coordination of the student on the way to mastering the techniques and methods of conducting successful communication. The study includes an analysis of the lesson, where the argumentative process is studied, and the structural and substantive organization, the compilation of verbal argumentative communication, depending on the topic of the short film, which is based on oral argumentative communication. The article offers recommendations on the organization of the process of teaching oral argumentative communication.